THE ROLE OF REFLECTING SURFACES IN ACHIEVING A DARK AND LUMINOUS EFFECT FOR VIDA BEKASI MARKETING OFFICE’S WORK-RELATED ACTIVITIES - Pradipta, Edward (Jurnal Riset Arsitektur, 2017)
Abstract- Lighting plays an important role in space formation and supporting activities. The utilization of natural lighting for the sake of saving energy can serve that purpose at noon. In the office, good natural lighting will support effienct use of energy by not using artificial lighting. The particular kind of sunlight that feels comfortable for office use should be the non-direct one which is reflected first. Therefore, the natural lighting design should pay attention to this, from the exterior to the interior elements, especially the reflecting surface providing non-direct sunlight.As one of Jakarta’s satellite cities, Bekasi’s development keeps increasing. New housing areas appear and require marketing offices as working areas and for image branding. The marketing office located in Vida Bekasi in East Bekasi uses no artificial lighting at noon. This research discusses what kind of role reflecting surfaces play in achieving a dark and luminous effect for Vida Bekasi marketing office’s work-related activities, by focusing on office rooms A and B. Room A on the first floor and room B on the second floor are interesting topics for discussion as they share the reflecting surface element even though the effect differs.This research can be classified as evaluative-descriptive, employing both the qualitative and quantitative methods. The research started off with interviews conducted with both the architect and the site architect, in addition to literature study, magazine articles, brochures, and internet sources. The calculations were made with a ruler and lux meter, and simulation was conducted with the Velux Daylight Visualizer 3.The analysis concludes that the reflecting surface configuration ranging from form and color to texture is one of the possible strategies to optimize natural lighting in offices.Keywords : natural lighting, reflecting surface, Vida Bekasi marketing office